Upaya Meningkatkan Kemampuan Kognitif dan Minat Belajar Peserta didik Melalui Gamifikasi Pembelajaran Pendidikan Agama Buddha Materi Hukum Kesunyataan Kelas XI SMA Negeri 1 Ampel Tahun Pelajaran 2022/2023 - Sidharta, Saddhiviharika Arya; Rispatiningsih, Dwi Maryani; Sujiono, Sujiono; Sudarto, Sudarto; Shadikah, Arina Afiyati; Purnomo, Danang Try; Harto , Sugik (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to describe the application of gamification of learning in improving the cognitive abilities of students on the material of the Law of Reality of Buddhist Religious Education Class XI SMA Negeri 1 Ampel for the 2022/2023 academic year. This research was conducted at SMA Negeri 1 Ampel for 10 weeks with a class action research model (PTK). The use of gamification of learning can improve students' cognitive abilities in Buddhist Education subjects. The learning model used in this study is learning gamification using the genially application. The results showed an increase in students' cognitive abilities after the implementation of learning gamification. Thus, the use of learning gamification can be an effective alternative in improving students' cognitive abilities and interest in learning in Buddhist Education subjects. Keywords: gamified , interest, learning, cognitive